Differential activation of ascending noxious pathways associated with trigeminal nerve injury. Issue 6 (June 2019) - Okada, Shinji; Katagiri, Ayano; Saito, Hiroto; Lee, Jun; Ohara, Kinuyo; Iinuma, Toshimitsu; Bereiter, David A.; Iwata, Koichi
Abstract : Abstract: Trigeminal spinal subnucleus caudalis (Vc) neurons that project to the ventral posteromedial thalamic nucleus (VPM) and parabrachial nucleus (PBN) are critical for orofacial pain processing. We hypothesized that persistent trigeminal nerve injury differentially alters the proportion of Vc neurons that project to VPM and PBN in a modality-specific manner. Neuroanatomical approaches were used to quantify the number of Vc neurons projecting to VPM or PBN after chronic constriction injury of the infraorbital nerve (ION-CCI) and subsequent upper-lip stimulation. Male rats received injections of retrograde tracer fluorogold into the contralateral VPM or PBN on day 7 after ION-CCI, and at 3 days after that, either capsaicin injection or noxious mechanical stimulation was applied to the upper lip ipsilateral to nerve injury. Infraorbital nerve chronic constriction injury rats displayed greater forelimb wiping to capsaicin injection and mechanical allodynia of the lip than sham rats. Total cell counts for phosphorylated extracellular signal-regulated kinase-immunoreactive (pERK-IR) neurons after capsaicin or mechanical lip stimuli were higher in ION-CCI than sham rats as was the percentage of pERK-IR PBN projection neurons. However, the percentage of pERK-IR VPM projection neurons was also greater in ION-CCI than sham rats after capsaicin but not mechanical lip stimuli. The present findings suggest that persistent trigeminal nerve injury increases the number of Vc neurons activated by capsaicin or mechanical lip stimuli. By contrast, trigeminal nerve injury modifies the proportion of Vc nociceptive neurons projecting to VPM and PBN in a stimulus modality-specific manner and may reflect differential involvement of ascending pain pathways receiving C fiber and mechanosensitive afferents. Abstract : Altered activation of ventral posteromedial thalamic nucleus/parabrachial nucleus projection neurons in Vc may reflect differential involvement of C fiber and mechanical afferents in trigeminal neuropathic pain.